Corps, image, expression. Réflexion à partir de Merleau-Ponty (Lebenswelt. Aesthetics and philosophy of experience., 2016)
The article aims at developing an analysis of some Merleau-Ponty’s thesis concerning art, perception and ontology, and takes freely the cue from his reflections.In a nutshell, it argues that the creative significance of expression is deeply linked to an essential process, namely the process in which the human body becomes an image.